STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF LAMELLAR MACULAR HOLES. Issue 11 (November 2019) - Nguyen, Justin H.; Yee, Kenneth M.P.; Nguyen-Cuu, Jeannie; Sebag, J.
Abstract : Purpose: Lamellar macular holes (LMHs) can been subdivided into tractional and degenerative subtypes. This cross-sectional cohort study compared structural and functional characteristics in these subtypes hypothesizing that tractional LMH has a higher prevalence of vitreopapillary adhesion and tangential traction (macular pucker), whereas degenerative LMH has more ellipsoid zone disruption and worse vision, measured three different ways. Methods: Tractional LMH (n = 22) and degenerative LMH (n = 15) were distinguished by optical coherence tomography criteria. Separate spectral domain optical coherence tomography scanning of the macula and optic disk was performed. Visual acuity, contrast sensitivity function (Weber Index, %W), and the degree of visual distortions (3-dimensional threshold Amsler grid; % volume lost [%VL]) were quantified. Results: Vitreopapillary adhesion was present in 14/22 (64%) tractional, but in only 3/15 (20%) degenerative LMH ( P = 0.006). Macular pucker was present in 19/22 (86%) tractional, but in only 8/15 (53%) degenerative LMH ( P = 0.011). Ellipsoid zone disruption was present in 13/15 (87%) degenerative, but in only 2/22 (9%) tractional LMH ( P = 0.0001). Visual acuity was better in tractional than degenerative LMH ( P = 0.006), as was contrast sensitivity function (tractional = 3.44 ± 1.07 %W, degenerative = 4.66 ± 1.73 %W; P = 0.015). Visual distortions were less in tractional (0.33 ± 0.61 %VL) than in degenerative (0.85 ± 0.68 %VL) LMH ( P = 0.014). Conclusion: Structure and visual function differ significantly in subtypes of LMH. Tractional LMH has 3-fold higher prevalence of vitreopapillary adhesion and 2-fold higher prevalence of macular pucker. Degenerative LMH has 9-fold more ellipsoid zone disruption, worse visual acuity and contrast sensitivity function, and 3-fold more distortions. Thus, outer retinal integrity seems more closely correlated with vision than anterior structural abnormalities in LMH. Abstract : Tractional lamellar macular holes have a greater prevalence of vitreopapillary adhesion (4-fold) and macular pucker (2-fold) than degenerative lamellar macular holes. Functionally, degenerative lamellar macular holes have worse visual acuity and contrast sensitivity function, as well as 3-fold more visual distortions, associated with a higher prevalence of ellipsoid zone disruption (87% vs. 9%).